2022
DOI: 10.3389/fmed.2022.910987
|View full text |Cite
|
Sign up to set email alerts
|

Anti-SARS-CoV-2 Revaccination Success in Kidney Transplant Recipients With No Initial Humoral Response Is Linked to Primary Vaccine Type

Abstract: BackgroundWhile anti-SARS-CoV-2 vaccination success in kidney transplant recipients (KTR) after two doses and 1273-mRNA was associated with higher seroconversion rates compared to BNT162b2-mRNA in our “DIA-Vacc Study” (NCT04799808), it remains unclear whether this may also be the case in non-responding KTR after a third vaccination dose.Materials and MethodsNon-responding KTR (after two mRNA vaccinations) were investigated 4.5–6 months after study enrollment at first vaccination. One hundred sixty-six of 193 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Type 3 due to nonrandomized studies j I 2 = 53.2%, Χ 2 = 12.81, p ( Q ) = 0.05; moderate heterogeneity k Wide 95% CI due to wide IQR and range for mean antibody levels per arm in Andreica et al [ 83 ] and Manjappa et al [ 85 ] l Lower grading due to imprecision and nonrandomized studies. No strong association identified, therefore type 4 m I 2 = 76.2%, Χ 2 = 54.56, p ( Q ) = 0; considerable heterogeneity n Wide 95% CI due to wide IQR for mean antibody levels per arm in Stumpf et al [ 75 ]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Type 3 due to nonrandomized studies j I 2 = 53.2%, Χ 2 = 12.81, p ( Q ) = 0.05; moderate heterogeneity k Wide 95% CI due to wide IQR and range for mean antibody levels per arm in Andreica et al [ 83 ] and Manjappa et al [ 85 ] l Lower grading due to imprecision and nonrandomized studies. No strong association identified, therefore type 4 m I 2 = 76.2%, Χ 2 = 54.56, p ( Q ) = 0; considerable heterogeneity n Wide 95% CI due to wide IQR for mean antibody levels per arm in Stumpf et al [ 75 ]…”
Section: Resultsmentioning
confidence: 99%
“…Type 3 due to nonrandomized studies j I 2 = 53.2%, Χ 2 = 12.81, p(Q) = 0.05; moderate heterogeneity k Wide 95% CI due to wide IQR and range for mean antibody levels per arm in Andreica et al [83] and Manjappa et al [85] l Lower grading due to imprecision and nonrandomized studies. No strong association identified, therefore type 4 m I 2 = 76.2%, Χ 2 = 54.56, p(Q) = 0; considerable heterogeneity n Wide 95% CI due to wide IQR for mean antibody levels per arm in Stumpf et al [75] GRADE analysis found that the certainty of evidence of the seroconversion outcome overall and in the solid organ transplant and autoimmunity subgroups was downgraded to type 4 (very low) due to imprecision and indirectness because different assays and antibody thresholds were used to assess and define seroconversion across the studies analyzed. Evidence certainty in the subgroup of patients with hematologic malignancies was retained as type 3 (i.e., the maximum certainty possible for nonrandomized studies), because there was a strong association in seroconversion likelihood and no issues with imprecision.…”
Section: Seroconversionmentioning
confidence: 93%
See 1 more Smart Citation
“…Four studies directly compared cellular immune responses in kidney transplant recipients vaccinated with mRNA versus the viral vector vaccine (34,42,43,53). Although comparison was not significant at <0.05, the pooled effect sizes and 95%CI for both two-and three-dose regimens demonstrated higher cellular immune response rates in kidney transplant recipients who received mRNA versus viral vector vaccines (Supplementary Figure S6).…”
Section: Comparison Of Cellular Immune Response Between Types Of Sars...mentioning
confidence: 99%
“…Although comparison was not significant at <0.05, the pooled effect sizes and 95%CI for both two-and three-dose regimens demonstrated higher cellular immune response rates in kidney transplant recipients who received mRNA versus viral vector vaccines (Supplementary Figure S6). Three studies performed head-to-head comparisons of BNT162b2 and mRNA-1273, two after a single dose and a complete primary vaccination series (25, 31) and one after a booster dose (53), which did not show a significant difference of cellular immune responses between these mRNA vaccines.…”
Section: Comparison Of Cellular Immune Response Between Types Of Sars...mentioning
confidence: 99%